Analisis Sentimen Opini Supporter Pengguna Youtube terhadap Sistem Pembelian Tiket Pertandingan Persib menggunakan Metode Naïve Bayes - Adam Arifian Alamyah; Rini Astuti; Fadhil Muhamad Basysyar (Universitas Wahid Hasyim, 2024)
Reporting about Persib cannot be separated from the role of the media from the era of the union until today. The first news about Persib in the media was at least in November 1904, when the Priangan Association (PVB) was recorded as the first association in Bandung. Using Descriptive Analysis, in the form of a word cloud, which is used in this research to identify and form word patterns that can be associated with other words that are considered important. Naïve Bayes Classifier Method. used in this research to identify and form word patterns that can be associated with other words to obtain information that is considered important. YouTube has become one of the largest platforms for sharing visual content on the internet. One of the topics that is being widely discussed is the ticket purchasing system for Persib Bandung matches. This has invited a lot of reactions, especially from the community, especially residents of West Java. This causes the controversy to become a polemic. Therefore, a method is needed to classify reviews automatically by conducting sentiment analysis. In this research, 2129 comment data in several contents discussed the Persib Bandung match ticket system. The aim of this research is to classify the analysis. review of the polemic of the match ticket system using the Naïve Bayes algorithm.